Chemical synthesis mono- and diacylglycerol from palm stearin-olein blend using continuous high shear stirred tank reactor - Elma Sulistiya; Rini Yanti; Chusnul Hidayat (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
This research aimed to evaluate the effect of flow rate and processing time on the synthesis of high mono- and diacylglycerol (MDAG) from palm stearin-olein blend using high shear continuous stirred tank reactor (HS-CSTR). Glycerolysis-interesterification was performed at 120 ºC and flow rates of 6, 10, 14, 18, and 22 mL/min. Glycerol:oil ratio, stearin:olein ratio, NaOH concentration, and agitation rate were 1:5 (mol/mol), 60:40 (w/w), 3%, and 2000 rpm, respectively. The result showed that flow rate significantly affected MDAG concentration and the product's physical characteristics. The highest MDAG was obtained at a flow rate of 6 mL/min. MDAG concentration, slip melting point (SMP), melting point (MP), hardness, emulsion capacity, and stability were 60.36 ± 1.61%, 42.3 ± 0.01 ºC, 43.3 ± 0.06 ºC, 6.04 ± 0.32 N, 87.6 ± 1.75 % and 91.8 ± 2.99 % respectively. An increase in residence time, which means flow rate decreased, increased MDAG, SMP, MP, hardness, emulsion capacity, and stability of the product. Processing time did not significantly affect MDAG concentration and the product's physical properties. It means that acylglycerol concentrations and physical properties of the product did not fluctuate significantly during the process. Thus, it confirmed that the continuous process was stable and reached a steady state throughout the process.